Aminoglycoside impregnated cement spacer precipitating acute kidney injury requiring hemodialysis. Issue 1 (31st July 2017) - Salim, Sohail Abdul; Everitt, Jessica; Schwartz, Aaron; Agarwal, Mohit; Castenada, Jorge; Fülöp, Tibor; Juncos, Luis A.
Abstract: The current standard of care for prosthetic joint infection includes two‐stage arthroplasty, with antibiotic‐impregnated cement spacers (ACS) utilized between the stages. We report a 75‐year‐old woman with previously normal renal function, who developed acute kidney injury (AKI) secondary to biopsy‐proven acute tubular necrosis and acute interstitial nephritis after ACS placement containing tobramycin and vancomycin. Peak tobramycin level measured 25.3 mcg/mL, the highest value reported in the literature after ACS placement. Intermittent hemodialysis was initiated with subsequent full recovery of renal function. This paper reviews the published literature regarding the accumulation, toxicity and removal dynamics of aminoglycoside (AG) antibiotics and vancomycin in renal patients. Obtaining serum AG level should be strongly considered in patients experiencing AKI after ACS. Renal replacement therapy may assist in reducing toxic AG levels.